Faktor-Faktor Yang Mempengaruhi Minat Menabung Mahasiswa di Bank Syariah - Nur Syamsi Adilla; Eliyanora; Desi Handayani (Jurnal Akuntansi Keuangan dan Bisnis, 2021)
This study aims to examine "The Influence of Income, Religiosity and Student Knowledge about Islamic Banks on Interest in Savings in Islamic Banks". This study uses a quantitative method with the type of causality research. The dependent variable of this study is interest in saving, while the independent variables consist of income, religiosity and student knowledge. The sample used in this study was 155 people, with the sampling technique using purposive sampling technique. The data collection method used is a questionnaire, then the results of the data are analyzed using multiple linear regression by conducting simultaneous significance test (F), coefficient of determination test, partial t test with a significance of 5% (α = 0.05) which is processed with program tools. SPSS Version 22.0 computer. The results showed that partially there was no effect of student income on interest in saving in Islamic banks and also partially for the variables of religiosity and student knowledge had a positive effect on interest in saving in Islamic banks. However, simultaneously income, religiosity and knowledge of students about Islamic banks have a positive effect on student interest in saving in Islamic banks. Therefore, it is expected that Islamic banks will always carry out continuous socialization about Islamic banks and also be accompanied by programs that can increase one's faith, so that people, especially students, can switch to Islamic banks. Keywords: income, religiosity, knowledge and interest in saving.